초등학교 내 학교구강보건실 운영 여부에 따른 아동의 치아우식경험도 비교 연구 - 임순환; Soon Hwan Lim; 김응권; Eung Kwon Kim; 권미영; Mi Young Gwon (Chiwisaeng gwahakoeji, 2005)
The study was intended to investigate elementary schoolers' oral health status according to whether the school have and manage an school oral health clinic or not in order to provide useful information for continuously developing the school oral health clinic 1,163 children in Hwasan elementary school in Hwasung city and 485 children in S elementary school in the same locality were selected as the experimental group and the control group, respectively, and orally examined from May 1st to 30th, 2004. The findings from the oral examination were as follows. 1. DMF rate was higher in the higher grades in both the groups. The rate was lower in the experimental group with 45.1% of the children than in the control group with 65.3% of the children. 2. DMFT rate also were higher as the grades were higher in both the groups. The ratio was lower in the experimental group with 30.4% of the children than in the control group with 44.6% of the children. 3. DMFT index was 1.0 in number in the experimental group and 1.6 in the control group. Index increase from the 1st grade to the sixth grade was also more positive in the experimental group. 4. DT rate was a little higher in the experimental group in the first graders, but comparatively decreased to the grades while increased in the control group. In the sixth graders, the rate was 42.4% in the experimental group and 87.7% in the control group, the former was less than the latter by about 50% point. 5. FT rate was a little higher in the control group for the first graders but increased in the experimental group to the grades. The rate in the sixth graders was higher by more than double in the experimental group. Based on the above findings, the region of the study had better oral health statistics than in other regions. The operation of school oral health clinics that provide dental health care to children at the right time seems to contribute to enhancing their dental health status by preventing against dental diseases and changing their relevant knowledge, attitude and behaviors. In the future, more school oral health clinics should gradually be prepared to push ahead with a sustained, extensive dental health project geared toward school-aged children. To make it happen, dental hygienists who are professional medical personnels should be taken advantage of, and in order to beef up the efficiency of preventive measures and oral health education, the best dental health care services should be offered by harnessing dental hygienists and dentists who work at public dental clinics run by local governments. 학교구강보건실 운영여부에 따라 초등학교 아동의 구강상태의 차이를 파악하여 학교구강보건사업을 지속적으로 발전시키기 위한 기초 자료를 제시하고자 실시한 본 연구는 사업군으로 화성시의 화산초등학교 아동1163명과 대조군은 동일 지역권 내의 S 초등학교 아동 485명을 대상으로 2004년 5월1일부터 5월 30일 까지 구강검사를 시행하였고 자료를 이용하여 얻어낸 결과는 다음과 같다. 1. 영구치 우식경험율은 두 군 모두에서 학년이 증가할수록 높아지며 특히 대조군에서 더 높고 사업군은 45%이며 대조군은 65%로 사업군이 낮게 조사되었다. 2. 우식경험영구치율도 두 군 모두에서 학년이 증가할수록 높아지는 경향이며 그 비율이 대조군에서 더 높고 사업군은 30.%이며 대조군은 44.0%로 사업군이 낮게 조사되었다. 3. 우식경험 영구치 지수는 사업군은 1.0개 대조군은 1.6개로 사업군이 낮고 1학년에서 6학년까지의 증가율도 사업군에서 훨씬 양호하였다. 4. 우식영구치율은 1학년 때에는 사업군에서 약간 높았던 것이 학년이 높아질수록 사업군에서 비교적 낮아지며 6학년에서는 사업군 42.0% 대조군 87.0%로 대조군보다 사업군에서 거의 50%이상 낮게 조사되었다. 5. 처치영구치율은 1학년 때에는 대조군에서 약간 높은 경향이었으나 학년이 높아질수록 사업군에서 높아지는 경향을 보이다가 6학년에서는 사업군에서 2배 이상 높았다. 이상의 결과를 검토한 결과 사업군에서 구강보건 상태가 매우 양호하게 나타났다. 이는 학교구강보건실 운영을 통하여 아동들에게 적기에 구강보건관리를 실시해 줌으로써 구강질환을 미리 예방하고 학생의 구강보건 지식과 태도 및 행동을 변화시켜 나타난 결과로 사료되는바 학교구강보건실을 점차적으로 확대 설치하여 학령기 아동에게 계속적으로 포괄적 구강보건예방 사업을 실행할 수 있어야 한다. 이를 위해서는 전문인력인 치과위생사를 적극 활용하여 아동들의 구강건강을 증진시켜야 할 것이며 또한 예방업무와 구강보건교육을 강화하기 위해서는 각 행정단위별로 배치되어 있는 공중보건치의사와 치과위생사를 적극 활용하여 구강건강관리를 최고에 달할 수 있도록 하여야 할 것이다.